Radio Power: An exploration of agency for the participants of a climate change communication campaign in South Africa - Petit-Perrot, Clémence (Graduate School of Business (GSB), 2023)
Communication for Development (C4D) appeared after World War 2 and has since become a key approach to achieving sustainable and democratic development, especially in the Global South. It borrows from behaviour economics and psychology, focusing mostly on behaviour change outcomes. While it has been effective in public health campaigns, it consistently fails at addressing more complex issues, or “wicked problems”, like as climate change. Inspired by agentic perspectives in development studies and the potential of radio as a critical thinking development, dialogue, and mobilisation tool, I wondered what the potential of communication for social change to activate agency in the face of wicked problems could be. I thus decided to explore the potential of media, and community-based radio projects to address wicked problems and catalyse agency. I studied the impact of a youth-led sustainable living radio campaign and its impact on its producers and listeners in three communities in South Africa to understand to what extent engagement with the campaign manifested agency within its producers and listeners. In the face of wicked environmental issues, collective agency emerged as the only potentially effective power to mobilise. I concluded that more participatory approaches are needed when designing and implementing communication for social change campaigns and recommend that agency be reconsidered as a practical and achievable short-term outcome with potential exponential impact, rather than the abstract long-term goal it's often envisioned as.